Epidemiological Surveillance of the ocular impairments in Hansen's Disease - Medina, Norma H. (2004)
An evaluation of data on ocular disabilities of leprosy registered cases in 1989, in São Paulo State, pointed that it was needed to change the criteria of diagnosis to improve sensibility at the time of detection. Since 1990, the Leprosy Program together with the Ophthalmology Service of São Paulo State, intensified training in detection, prevention and treatment of the ocular disabilities. A group of experts designed a new standardization of procedures and criteria for grading of the ocular disabilities in accordance with the WHO guidelines. The Leprosy notification forms were analyzed for the years 1989, 1993 and 1996 with the objective to evaluate the changes of criteria. In 1989, 3210 leprosy cases were notified, the frequency of ocular disabilities in those cases was 72 (2.2%). During 1993, of the 2927 leprosy cases notified, the frequency of ocular disabilities was 130 (5.3%). In 1996, 2915 cases were notified and the frequency of ocular disabilities was 164 (6.9%). The MB cases showed a greater proportion of ocular disabilities than the PB (p < 0.05). The changes in the forms for the diagnosis of the ocular disabilities, detected at the time of the notification, and the training of personnel, contributed to the increase of the number of cases with ocular disabilities, mainly in grade 1 (corneal hypostesia) and grade 2 (Iagophthalmos, trichiasis, corneal opacification). This increase does not indicate worsening of the endemic disease neither later diagnosis, just operational improvement.